Insight into the dynamics of electro-magneto-hydrodynamic fluid flow past a sheet using the Galerkin finite element method: Effects of variable magnetic and electric fields - Qamar, Izza; Farooq, M. Asif; Irfan, M.; Mushtaq, Asif (Frontiers in Physics, 2022)
The influence of Arrhenius activation energy and variable thermal conductivity with EMHD and bionanofluid over a nonlinearly radiating stretching sheet in a porous medium is analyzed. The fundamental laws i.e. conservation of mass, momentum, and energy equations are given in the form of partial differential equations (PDEs). redThe current fluid flow problem is not similar which means that the presented solution is local. The introduction of non-similarity variables transforms PDEs into a set of coupled ODEs. The resultant ODEs are not only solved computationally by MATLAB built-in solver bvp4c but the solution is also obtained with other numerical schemes that include the shooting method and the Finite Element Method (FEM). redIn applying FEM, we choose the Galerkin method in which the weight function is equal to the shape function. The aforementioned numerical methods are implemented and programmed in MATLAB. Graphs illustrate the effects of various parameters on the velocity, temperature, concentration, and microorganism profiles. Physical parameters that measure the roughness of the sheet (skin friction coefficient), heat transfer rate at the sheet (local Nusselt number), the mass transfer rate of the concentration gradient (local Sherwood number), and transfer rate of microorganisms at the sheet (density of motile microorganism). The skin friction coefficient increases for higher values of (K_p) and magnetic parameters (M). The local Sherwood number decreases for different values of activation energy. redAn excellent agreement of FEM results with other numerical methods, shooting method and bvp4c, have been achieved. Moreover, for particular cases, the current results give a good agreement with the published work